Survival outcomes in isolated severe tricuspid regurgitation according to therapeutic modalities: a systematic review and meta-analysis - Bernard Iung; Gregory Ducrocq; Dominique Himbert; Marina Urena-Alcazar; Dimitri Arangalage; Alec Vahanian; Eric Brochet; Gaspard Suc; Clémence Delhomme; Jules Mesnier; Audrey Cailliau; Mustafa Habib (Open Heart)
Importance Managing isolated severe tricuspid regurgitation (TR) poses significant challenges, with questions recently arising about the efficacy of surgery and percutaneous therapies compared with conservative approaches in improving survival.Objective We aimed to assess the available evidence on mortality associated with different treatment modalities for isolated severe TR.Evidence review A comprehensive search of medical databases was conducted. Studies reporting mortality of isolated TR at 1-year follow-up, with TR severity classified as moderate-to-severe or worse, were included. Exclusion criteria were TR associated with left-heart disease and combined procedures (treating other valves). The primary endpoint was all-cause mortality at 1 year, with secondary outcomes including in-hospital, 2-year and 5-year mortality. Mortality was compared by meta-analysis and meta-regression using age, sex and left ventricular ejection fraction as confounders.Findings 25 studies met the inclusion criteria. Mean age was 72.0 years among the 5702 patients managed medically, 71.3 years among the 1416 patients treated percutaneously and 59.3 years among the 1990 patients managed surgically. In medically managed patients, 1-year, 2-year and 5-year mortality rates were 14%, 20% and 46%, respectively. Among percutaneously managed patients, there was an in-hospital mortality of 1% and a 1-year mortality rate of 18%, which increased to 22% at 2 years. Surgically managed patients experienced an in-hospital mortality of 8% with 1-year, 2-year and 5-year mortality rates of 15%, 20% and 30%, respectively. No statistical differences in mortality were observed at 1, 2 or 5 years. Those results were confirmed after adjusted meta-regression.Conclusions These findings underscore the significant long-term mortality associated with isolated severe TR, regardless of treatment group. Despite potential selection bias, both percutaneous and surgical interventions did not offer lower mortality rates compared with medical management after 2 years. Further research is warranted to improve outcomes in the management of isolated TR.